Autenticação e Controle de Acesso na Arquitetura ETArch - Melo, Pedro H. A. Damaso; Silva, Flávio de O.; Rosa, Pedro F. (Anais do Workshop de Pesquisa Experimental da Internet do Futuro (WPEIF), 2017)
Despite of evolutions, the current Internet can not adequately handle requirements such as multihoming, QoS, mobility, multicast and security. Several research groups around the world are involved in creating, experimentally and incrementally, the next generation of Internet architecture. A Brazilian initiative in this area is the Entity Title Architecture (ETArch) whose prototype is based on the concept of Software Defined Networking and uses the OpenFlow protocol. This work presents two contributions implemented in ETArch, being an authentication mechanism and an access control, whose trade-off is presented in this work.